Early parastomal evisceration of small bowel following a loop ileostomy for malignant intestinal obstruction. (May 2021) - Basnayake, Oshan; Prasanthan, Y; Jayarajah, Umesh; Ganga, NMPG; De Silva, Kanishka
Evisceration of bowel through the stoma is a rare complication and only few cases have been reported. Although most cases occur in the context of long-standing parastomal hernias, early evisceration may also occur causing significant morbidity to patients. The reported patient is a 53-year-old male with bronchial asthma who was diagnosed to have metastatic colonic cancer underwent a trephine loop ileostomy for intestinal obstruction. On post-operative Day 7, he developed small bowel evisceration through the ileostomy site. The patient underwent an emergency laparotomy and found to have non-viable prolapsed small bowel segment at the stoma site. Furthermore, there were extensive peritoneal deposits and large para aortic lymph node mass and ascites compromising the peritoneal space. Resection of non-viable small bowel and ileostomy refashioning was carried out. The patient was managed in the intensive care unit and he gained function of the ileostomy on post-operative Day 2. On Day 5, he died due to subsequent pneumonia and worsening acute respiratory distress syndrome. Early parastomal evisceration is an extremely infrequent life-threatening complication that requires urgent treatment. Disseminated cancer, bowel obstruction, poor nutritional status, ascites and exacerbation of bronchial asthma were additional risk factors in our patient.